Sustainability assessment for corporate management of energy production and supply companies for Lithuania - Stasiškienė, Žaneta; Šliogerienė, Jūratė (International Journal of Strategic Property Management, 2009)
Corporate responsibility has become an important issue for management to address. The responsibility of the organization for the public environment (ecological, social and economic aspects of the environment) has become a matter of management attention referring to the entire organization and all major stakeholders. Therefore safe, environmentally sound, and economically viable energy production and supply should be essential part of management issues. The anticipated closure of the Ignalina Nuclear Power Plant at 2009 will change the situation of electricity generation in Lithuania significantly. The costs of electricity generation and distribution are the most important criteria shaping decisions in the energy production and supply companies. Sound energy and environmental accounting must be the basis of any strategic decision making in order to keep up with the increasing complexity of energy and environmental problems. Efficiency, equity, ecological integrity, and technological change are introduced as fundamental aspects that need to be considered in a comprehensive sustainable energy production and supply framework. Since these issues cannot be suitably included within the frame of a single model, a combination of ecological, economic, technological and social measures for different aspects of Lithuanian energy system and sustainable development are analysed.First Publish Online: 18 Oct 2010